New perspectives in English plus - Fernando, Jovita N.; Habana, Pacita I.; Cinco, Alicia L. (Manila, Philippines : Rex Book Store, 2005)
New perspectives in English plus is a holistic approach to language. It integrates listening, speaking, reading, and writing activities by organizing them around seven compelling contemporary themes. The textbook is developed from a tri-dimensional syllabus integrating communicative, grammatical, and critical thinking objectives.
Unit I. Parts of Speech -- Unit II. The simple tenses -- Unit III. The perfect or compound tenses -- Unit IV. Phases and Clauses -- Unit V. Sentence patterns -- Unit VI. Sentence construction.
Includes bibliographical references and index.
Keywords: ENGLISH LANGUAGE -- GRAMMAR